Audit Committees and Audit Fees: An Empirical Study in Large French Listed Companies - Lobna Loukil (STIE Malangkucecwara, 2014)
This study examines, in a French setting, the impact of the presence and two attributes associated with effectiveness of the audit committee on the magnitude of audit fees. The sample used to test the impact of the presence of an audit committee was a panel of 106 SBF 250 French firms over a period of 6 years (2002-2007). The sample was reduced by focusing on only those firms with an audit committee. That sub-sample was used to test the impact of the level of independence of the audit and the frequency of its meetings on the level of audit fees. The random effects regression results show that the existence and independence of an audit committee and the frequency of its meetings have a positive and significant effect on the audit fees. Theoretically, the results show a complementary relationship between these variables, which means the more detailed work of an external auditor, complements the work of an effective audit committee.